QUR’ANIC PERSPECTIVE ON TOTAL QUALITY MANAGEMENT (TQM) AND ITS IMPLEMENTATION IN THE INSTITUTION OF ISLAMIC EDUCATION - Saihu, Saihu (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2020)
This paper discusses the Total Quality Management (TQM) that needs to be done at educational institutions as a form of efforts to improve the quality of education. This paper focuses on the perspective of the Qur'an and the Hadith as a foundation in implementing TQM in order to gain the trust of the community and stakeholders. One way to keep getting this is by making continuous improvements, both from physical and non-physical aspects. So that it becomes a quality educational institution and guaranteed quality. Some TQM principles that must be implemented in the world of education are 1) Setting Quality Standards, (Quality assurance); 2) Change of culture; 3) Organizational change (upsidedown-organization); and 3) Maintaining relationships with customers (keeping close to the customer). The concept of quality in management education is in accordance with the Qur'an and the Hadith of the Prophet. The reference to quality in the Qur'an is the word ihsan. Ihsan means quality that has implications for the quality of the process, the quality of planning and control, which in turn produces a quality development framework in accordance with the Qur'an and Hadith.